On two weight estimates for iterated commutators. - Lerner, Andrei; Ombrosi, Sheldy J.; Rivera Ríos, Israel P. (Elsevier, 2021)
In this paper we extend the bump conjecture and a particular case of the separated bump conjecture with logarithmic bumps to iterated commutators . Our results are new even for the first order commutator . A new bump type necessary condition for the two-weighted boundedness of is obtained as well. We also provide some results related to a converse to Bloom's theorem.
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/11374
Keywords: Calderón-Zygmund, Operadores de; Commutators; Calderón-Zygmund operators; Sparse operators; Weighted inequalities